Implementasi Model Contextual Teaching and Learning Berbantuan Video dalam Pembelajaran Bahasa - Rupita, Sari; Jumhur, Jumhur; Irmansyah, Irmansyah; Saputra, Bayu; Sholekhah, Amilatus (Universitas Muhammadiyah Magelang, 2025)
The purpose of this study is to implement the contextual teaching and learning (CTL) model in Arabic language lessons, namely to help students relate learning materials to real life, so that students can easily apply the material taught in their daily lives, and learning using videos makes students more enthusiastic and enthusiastic in participating in learning, because learning is not monotonous so that students do not get bored quickly during learning and learning becomes more effective. The method used in this study was mixed methods involving the collection of quantitative and qualitative data to obtain a more complete picture of the effectiveness of the CTL model with videos in improving students' motivation and Arabic language skills. The application of the CTL model with videos has been proven to significantly increase students' learning motivation and their Arabic language skills according to the results of the study. In addition, the CTL model also helps students develop their social skills through group learning and materials that relate to real life. This study concludes that the CTL learning model using videos is an alternative method that increases the effectiveness of the learning process. In this study, the use of media in the form of videos makes students more involved in the learning process, making learning more interesting and interactive. In addition, the CTL model with videos makes their thinking skills more critical and creative through discussion and group work.